Abrasive-Free Polishing of Single-Crystal 4H-SiC with Silica Glass Plates. (30th October 2015) - Kubota, Akihisa; Hatasako, Yuta; Takita, Takahiro; Touge, Mutsumi
Abstract : In this study, abrasive-free polishing of a single-crystal 4H-SiC (0001) substrate was investigated. Two different types of polishing plates, namely a synthetic SiO2 glass (quartz) plate and a soda-lime SiO2 glass plate, were used to polish the SiC substrate under atmospheric conditions at room temperature. The surface roughness after polishing was evaluated by differential interference contrast microscopy, phase-shift interferometric microscopy, and atomic force microscopy. In addition, the chemical bonding states of the SiC surface before and after polishing were analyzed by X-ray photoelectron spectroscopy. The experimental results showed that an oxide layer was formed on the SiC surface as a result of the chemical reaction between the interfaces of the synthetic SiO2 glass plate and the SiC substrate. This generated oxide layer was effectively removed by polishing with the soda-lime SiO2 glass plate, resulting in an atomically smooth SiC surface with a root mean square roughness of less than 0.1 nm for 1.5 h. Obtained experimental results indicate that the component materials, temperature and water adsorptive property of the soda-lime SiO2 glass play an important role in the removal of the tribochemically generated layer on the SiC surface during this polishing.